CARNIVAL FASHION CREATIVITY AT MALANG FLOWER CARNIVAL (MFC) - Sunandar, Agus; Dharsono, Dharsono (ISI Press Institut Seni Indonesia Surakarta, 2020)
Malang Flower Carnaval (MFC) which has worldwide, the results of the creation of these activities have been staged in various countries in the world. MFC has successfully entered the COE (Calender of Event) of the Indonesian Ministry of Tourism 3 times. The existence of this event supports and strengthens the predicate of Malang City as a Creative City in Indonesia. This success is interesting to do a study of how the fashion creativity that has been created from the MFC. This study uses a qualitative approach specifically Roland Barthes's fashion function theory and Edmund Burke Feldman's function theory of art. The results of the study showed that the creativity of the carnival dress appeared in the visualization of the shape of hair such as temples, gold ornaments, ornamental elements, and body gestures that symbolized the beauty of local dance. In addition, the carnival costumes can be a representation of local culture as an idea of creation. Implementation of a fashion carnival can encourage community creativity which ultimately increases public welfare.